The Development of Lecture Maker Applications in Arabic Language Learning for Elementary School - Widayanti, Rizka; Mudinillah, Adam; Amrina, Amrina; Ramadhanti Febriani, Suci; Yusuf Salam, Muhammad; Rezi, Melisa; Dewi, Yelfi; Kddour Guettaoui Bedra (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
The research aimed to produce and develop a Lecture Maker-based learning media in Arabic subjects for Islamic elementary school students, which was in accordance with the eligibility criteria for learning media that was valid, practical and effective. The type of research used Research and Development (R&D). The research model used ADDIE (analysis, design, development, implementation, and evaluation). The results of the research that showed that, (1) the validation results obtained in the use of Lecture Maker-based learning media showed a value of 4.22 which included in the 'valid ' category. (2) Based on the average teacher response showed the number 4.6 this meant that the Lecture Maker-based learning media was 'very valid'. While the average percentage was 92.00% which indicated that the media produced could be said to be practical to use. (3) Based on the analysis of students' cognitive results, it could be seen that classical learning completeness reaches 87.5% which indicates there was an increase in student learning outcomes using Lecture Maker-based learning media. So, it can be concluded that the screen Lecture Maker used in making Arabic learning media in order to increase learning motivation and student learning outcomes.